Reclaiming the Classics for a Diverse and Global World Through OER - Bird, Jessalynn; Blagburn, Brittany; Osborne, Marirose (KULA)

(untitled) (University of Victoria Libraries, 2022)
In the 2019–20 academic year, I redesigned a course on the classics to make both the texts and the context in which they were taught more accessible for and relevant to the predominantly female students of Saint Mary’s College, Notre Dame. The course was re-centered on the dialogue between the ever-evolving and diverse cultures within Greece and the Roman empire and surrounding regions such as Egypt, Ethiopia, and Persia; issues caused by slavery and economic inequality; conceptions of gender roles and sexuality, race and ethnicity, and migration and citizenship; the troubling appropriation of classical motifs and texts by fascist groups in the twentieth century and some alt-right groups and sexual predators in the twenty-first century; and on recent initiatives meant to demonstrate the diversity of both Greek and Roman cultures through documentary, artistic, and archaeological evidence (particularly in the digital humanities and in museums and libraries).  I also wanted to make the course close to zero cost for students and to shift to digital texts which lent themselves to interactivity and social scholarship. Our librarian, Catherine Pellegrino, obtained multi-user e-books for modern reinterpretations of classical works still in copyright. A LibreTexts grant enabled the co-authors of this article—the course instructor (and lead author) and two paid student researchers—and a team of summer-employed student collaborators to edit, footnote, and create critical introductions and student activities for various key texts for the course. Many of these texts are now hosted on the LibreTexts OER platform.  Beta versions of enriched OER texts and activities were user tested in a synchronous hybrid virtual/physical classroom of twenty-five students, who were taking the course (HUST 292) in the fall semester of 2020.